Validated SNAP markers based on the CYP P450 87 A3 gene in coconut (Cocos nucifera) are associated with yearly stem height increase - ANDI NADIA NURUL LATHIFA HATTA; DEWI SUKMA; ISMAIL MASKROMO; SUDARSONO SUDARSONO (Society for Indonesian Biodiversity, 2023)
Abstract. Hatta ANNL, Sukma D, Maskromo I, Sudarsono S. 2023. Validated SNAP markers based on the CYP P450 87 A3 gene in coconut (Cocos nucifera) are associated with yearly stem height increase. Biodiversitas 24: 2503-2512. Tall and dwarf coconuts are coconut types used worldwide as the parents in hybrid coconut production, and they differ in their yearly stem height. The yearly stem height of coconuts is estimated as 11 leaf scars length. The CYP P450 87 A3 gene is essential in the yearly stem-height increase (YSI) character. This study aims to validate single nucleotide-amplified polymorphism (SNAP) markers based on sequence variabilities of the coconut CYP P450 87 A3 gene and analyze their association with the coconut YSI character. The CYP P450 87 A3 partial genomic fragments were PCR amplified, sequenced, and used to develop SNAP markers. The markers were subsequently validated using 155 samples of 31 coconut varieties. The analysis showed that at least 17 single nucleotide polymorphisms (SNPs) exist in the exon-1 and 2 of the coconut CYP P450 87 A3 gene, and SNAP markers were successfully developed. Single-locus analysis showed that the validated CYP2_SNP1 SNAP marker locus was associated with coconut YSI characters. The developed SNAP marker based on the partial CYP P450 87 A3 gene can potentially support future marker-assisted selection (MAS) in coconut breeding, especially for developing coconut with low YSI character.